Legal Compliance in the Registration and Issuance of Halal Certificates in Indonesia: A Comparative Study with Malaysia - Afdhal, Afdhal; Syamsuri, Andi Santri; Sari, Mutiara Dwi (Al-Bayyinah, 2025)
This research comparatively analyzes the legal compliance frameworks governing the registration and issuance of halal certificates in Indonesia and Malaysia, two leading nations in the global halal market. It focuses on the normative juridical aspects, examining statutory provisions, institutional roles (BPJPH-MUI in Indonesia, JAKIM in Malaysia), and procedural mechanisms. The study highlights the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia in navigating these regulations, particularly in light of Law No. 33 of 2014 and its implementing regulations. Employing a qualitative approach with statutory, case study, and literature review analyses, the research identifies key differences in regulatory centralization, enforcement strategies, and MSME support systems. Findings indicate that while both nations strive for robust halal assurance, variations in legal implementation significantly impact compliance accessibility and economic implications for businesses. The study concludes with recommendations for enhancing legal certainty and streamlining compliance, particularly for Indonesian MSMEs, drawing lessons from Malaysia's more integrated system.